Thermal performance and entropy generation analysis of hybrid nanofluids in a 3D cylindrical microtube: Implications for biomedical applications - Chenxu Duan; Hassan Roshani; Payam Jalili; Bahram Jalili; Irshad Ahmad; Qasem M Al-Mdallal; Pan Zhang (Case Studies in Thermal Engineering)
This study presents a numerical analysis of transient natural convection, heat transfer, and entropy generation in a 3D cylindrical microtube containing a hybrid nanofluid with potential applications in biomedical engineering, such as targeted drug delivery and microfluidic heat exchangers. The analysis spans the time interval of 0 ≤ t ≤ 1.5 s and is based on dimensionless parameters, including Reynolds number, Richardson number, nanoparticle volume fraction, and Prandtl number. The hybrid nanofluid, composed of Al₂O₃ (5 %) and Cu (3 %) nanoparticles suspended in water, enhances flow and heat transfer characteristics, making it suitable for high-precision thermal management in micro-scale biomedical systems. Galerkin's finite element method is employed to solve the governing equations for flow behavior, temperature distribution, and entropy generation. Results indicate that increasing Reynolds and Richardson numbers intensifies flow and enhances velocity magnitudes, which is crucial for optimizing drug transport and thermal efficiency in microdevices. Additionally, entropy generation decreases with increasing Richardson number but rises with Reynolds number, while the average Nusselt number improves with both parameters, ensuring effective heat transfer performance in medical devices.